High-throughput sequencing reveals extraordinary fluidity of miRNA, piRNA, and siRNA pathways in nematodes - Shi, Zhen; Montgomery, Taiowa A.; Qi, Yan; Ruvkun, Gary (Genome Research, 2013)
The nematode Caenorhabditis elegans contains each of the broad classes of eukaryotic small RNAs, including microRNAs (miRNAs), endogenous small-interfering RNAs (endo-siRNAs), and piwi-interacting RNAs (piRNAs). To better understand the evolution of these regulatory RNAs, we deep-sequenced small RNAs from C. elegans and three closely related nematodes: C. briggsae, C. remanei, and C. brenneri. The results reveal a fluid landscape of small RNA pathways with essentially no conservation of individual sequences aside from a subset of miRNAs. We identified 54 miRNA families that are conserved in each of the four species, as well as numerous miRNAs that are species-specific or shared between only two or three species. Despite a lack of conservation of individual piRNAs and siRNAs, many of the features of each pathway are conserved between the different species. We show that the genomic distribution of 26G siRNAs and the tendency for piRNAs to cluster is conserved between C. briggsae and C. elegans. We also show that, in each species, 26G siRNAs trigger stage-specific secondary siRNA formation. piRNAs in each species also trigger secondary siRNA formation from targets containing up to three mismatches. Finally, we show that the production of male- and female-specific piRNAs is conserved in all four species, suggesting distinct roles for piRNAs in male and female germlines.